Evaluación de la actividad de adsorción a través de estructuras capilares de compuestos de origen fenólico en muestras de soluciones acuosas provenientes del canal arzobispo en Bogotá D.C. (2023)
Taking into account that phenolic compounds are substances that are harmful to human health and the environment, which enter water bodies through effluents from industrial or agricultural processes, the adsorption activity of the structures was analyzed. capillaries for the removal of these in aqueous solutions; Nine experiments were carried out, where the behavior of time and temperature with respect to absorbance and therefore the concentration of phenols in determined samples was studied.